HUBUNGAN KONTROL DIRI DAN KONFORMITAS TEMAN SEBAYA DENGAN PERILAKU HEDONISME DI SMP NEGERI 1 SOLOK - Adella Hafifah Fitri; Syawaluddin; Arjoni; Yeni Afrida (STKIP Subang, 2024)
This research was motivated by a phenomenon that occurred among students at SMP Negeri 1 Solok, where it was indicated that some students had difficulty controlling themselves to have a hedonistic behavior, and it was indicated that some students were influenced by peers who had a hedonistic behavior. This research aims to determine the relationship between self-control and hedonistic behavior, determine the relationship between peer conformity and hedonistic behavior and to determine the relationship between self-control and peer conformity and hedonistic behavior in class VIII students at SMP Negeri 1 Solok. This research uses a quantitative approach with a correlation type. The population in this study was class VIII students, totaling 89 students with indications of hedonistic behavior obtained from the results of a simple questionnaire. The sampling technique in this research used a total sampling technique by taking the entire population, namely 89 students. The instruments used in this research were the Hedonistic Behavior measurement scale, the Self-Control measurement scale and the Peer Conformity measurement scale. Data analysis used to test the research hypothesis is the multiple correlation test. The results of this study show that self-control (X1) with hedonistic behavior (Y) has a significant relationship with a value of 0.000 <0.05 and interpretation is in the medium category with a value of 0.448. Furthermore, peer conformity (X2) with hedonistic behavior (Y) has a significant relationship with a value of 0.000 <0.05 and interpretation is in the medium category with a value of 0.553. Furthermore, self-control (X1) and peer conformity (X2) are simultaneously and significantly related to the probability value (sig. F change) = 0.000 < 0.05 on hedonistic behavior (Y), and a correlation coefficient value is obtained in the strong category with a value of 0.673 .